If 2 0 1 7 x 2 + 2 0 1 8 x + 5 6 + 2 0 1 7 x 2 + 2 0 1 8 x − 5 6 = 1 1 2 , determine the value of 2 0 1 7 x 2 + 2 0 1 8 x + 5 6 − 2 0 1 7 x 2 + 2 0 1 8 x − 5 6
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The last line is incorrect.
You should still verify that there is a solution to the condition of the problem.
Log in to reply
thanks. There was an error when I made the solution.
2 0 1 7 x 2 + 2 0 1 8 x + 5 6 + 2 0 1 7 x 2 + 2 0 1 8 x − 5 6 = 1 1 2 . . . ( 1 )
⟹ 2 0 1 7 x 2 + 2 0 1 8 x + 5 6 = 1 1 2 − 2 0 1 7 x 2 + 2 0 1 8 x − 5 6 . . . ( 1 a )
Using ( 1 a ) , we have:
2 0 1 7 x 2 + 2 0 1 8 x + 5 6 − 2 0 1 7 x 2 + 2 0 1 8 x − 5 6 = 1 1 2 − 2 2 0 1 7 x 2 + 2 0 1 8 x − 5 6 . . . ( 2 )
From ( 1 ) × ( 2 ) :
2 0 1 7 x 2 + 2 0 1 8 x + 5 6 − ( 2 0 1 7 x 2 + 2 0 1 8 x − 5 6 ) 1 1 2 ⟹ 1 1 2 − 2 2 0 1 7 x 2 + 2 0 1 8 x − 5 6 2 0 1 7 x 2 + 2 0 1 8 x + 5 6 − 2 0 1 7 x 2 + 2 0 1 8 x − 5 6 = 1 1 2 ( 1 1 2 − 2 2 0 1 7 x 2 + 2 0 1 8 x − 5 6 ) = 1 1 2 ( 1 1 2 − 2 2 0 1 7 x 2 + 2 0 1 8 x − 5 6 ) = 1 from ( 2 ) = 1
Take reciprocal of 1st equation and rationalize the denominator
Problem Loading...
Note Loading...
Set Loading...
Let 2 0 1 7 x 2 + 2 0 1 8 x + 5 6 = p 2 0 1 7 x 2 + 2 0 1 8 x − 5 6 = q
1 1 2 ( p − q ) = ( p + q ) ( p − q ) 1 1 2 ( p − q ) = p 2 − q 2 1 1 2 ( p − q ) = ( 2 0 1 7 x 2 + 2 0 1 8 x + 5 6 ) 2 − ( 2 0 1 7 x 2 + 2 0 1 8 x − 5 6 ) 2 1 1 2 ( p − q ) = 2 0 1 7 x 2 + 2 0 1 8 x + 5 6 − ( 2 0 1 7 x 2 + 2 0 1 8 x − 5 6 ) 1 1 2 ( p − q ) = 2 0 1 7 x 2 + 2 0 1 8 x + 5 6 − 2 0 1 7 x 2 − 2 0 1 8 x + 5 6 1 1 2 ( p − q ) = 1 1 2 p − q = 1
So, 2 0 1 7 x 2 + 2 0 1 8 x + 5 6 − 2 0 1 7 x 2 + 2 0 1 8 x − 5 6 = 1 .